In vitro permeation studies of phenolics from horse chestnut seed gels prepared with different polyacrylic acid polymer derivatives - Zelbienė Eglė; Draksiene Gailute; Savickas Arunas; Kopustinskiene Dalia; Masteikova Ruta; Bernatoniene Jurga (Acta Pharmaceutica)
The aim of this study was to investigate the effects of polyacrylic acid polymers (Ultrez 10, Ultrez 20, Carbopol 980, and Carbopol 940) on the viscosity and the in vitro permeation of phenolic compounds from the gel prepared from natural horse chestnut seed extract. Experiments were performed in the presence and in the absence of peppermint oil (Mentha piperita). Our results showed that peppermint oil decreased the viscosity of the gels and permeation of phenolic compounds from all gel samples. Results show that the highest content of phenolic compounds (1.758 μg cm-2) permeated in vitro from gel based on Carbopol Ultrez 20 without peppermint oil added (p < 0.05 vs. other tested polymers).